Rancang Bangun Aplikasi Rekam Medis Berbasis Web Pada Rumah Sakit Mata Masyarakat Surabaya - Putra, Vito Ganesha; Lusiani, Titik; Mujayana, Marya (Jurnal Sistem Informasi Universitas Dinamika (JSIKA), 2017)
Rumah Sakit Mata Masyarakat is a technical services unit that held the overall eye health services. The integrated process using appropriate technologies that supported the active participation of community, cooperation across programs and across sectors. Patient registration system that accumulate resulting in the registration queue for hospital treatment. Registration system caused by the piling up of patients who come to the hospital too much at certain hours so make many patients queuing for too long. Patient registration system that accumulate resulting in the registration queue for hospital treatment. Registration system caused by the piling up of patients who come to the hospital too much at certain hours so make many patients queuing for too long.This study provides a solution that is the need for an application that can help process the queue, the process of recording, storage process and the payment of medical records.This research can be summed up as an application that features patient registration, login patients, the estimated waiting time of patients, the medical records of patients, take notice of medical records, and payment details.